2022
DOI: 10.1101/gr.276064.121
|View full text |Cite
|
Sign up to set email alerts
|

Functional noncoding SNPs in human endothelial cells fine-map vascular trait associations

Abstract: Functional consequences of genetic variation in the noncoding human genome are difficult to ascertain despite demonstrated associations to common, complex disease traits. To elucidate properties of functional noncoding SNPs with effects in human endothelial cells (ECs), we utilized our previous molecular quantitative trait locus (molQTL) analysis for transcription factor binding, chromatin accessibility, and H3K27 acetylation to nominate a set of likely functional noncoding SNPs. Together with information from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Finally, GWAS studies have established that hundreds of independent common genetic variants in human populations affect risk for CAD, yet discovering the causal mechanisms remains a major challenge given that most of the risk is in non-coding regions of the genome. One approach to prioritize causal variants in regulatory elements is through integration of open chromatin regions from the cell type and states of interest followed by expression quantitative trait loci (eQTL) or other linking evidence to target gene (75, 76). In the current study, we find significant enrichment for CAD-risk variants in open chromatin regions across the entire dataset (“panEC”) as well as specifically for EC2 and EC4 subpopulations (Figure 6B ; Table S15-17 in the Data Supplement ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, GWAS studies have established that hundreds of independent common genetic variants in human populations affect risk for CAD, yet discovering the causal mechanisms remains a major challenge given that most of the risk is in non-coding regions of the genome. One approach to prioritize causal variants in regulatory elements is through integration of open chromatin regions from the cell type and states of interest followed by expression quantitative trait loci (eQTL) or other linking evidence to target gene (75, 76). In the current study, we find significant enrichment for CAD-risk variants in open chromatin regions across the entire dataset (“panEC”) as well as specifically for EC2 and EC4 subpopulations (Figure 6B ; Table S15-17 in the Data Supplement ).…”
Section: Discussionmentioning
confidence: 99%
“…TeloHAEC and HepG2 cell lines were used for the experiment. STARR-Seq library and experiment have been described previously in 22,24,25 . To assess transcriptional activity of haplotypes of the candidate regulatory regions, STARR-Seq RNA read data was UMI-deduplicated, depth-normalized to library size, and normalized for haplotype abundance in the plasmid DNA (input) library.…”
Section: Methodsmentioning
confidence: 99%
“…TeloHAEC were cultured using Vascular Cell cocktail by pipetting up and down several times and incubated on ice for 15 minutes. 25 μl detergent (10% NP40) was added and vortexed for 10 seconds at highest setting.…”
Section: Materials and Methodmentioning
confidence: 99%
“…This study identified 2 SNPs at a GWAS locus for AAA located at the 3ʹ end of the LDAH gene; targeted deletion of the enhancer region containing both SNPs resulted in lower LDAH expression, without affecting other genes in the locus. 47 To our knowledge, similar studies have not yet been published for thoracic aortic variants; however, these initial reports offer a roadmap for combining traditional fine-mapping with sophisticated epigenomic techniques as well as high-throughput reporter assays to inform causal variant discovery.…”
Section: Fine-mappingmentioning
confidence: 96%